AVALIAÇÃO RESPIRATÓRIA DOS PORTADORES DE SÍNDROME DE DOWN - Strassburger, Simone Z.; Pretto, Luciana M.; Pasqualoto, Adriane S.; Wilkelmann, Eliane R.; Dalsochio, Clarissa (Salão do Conhecimento, 2013)
Resumo